The Main Street Lending Program - David M. Arseneau; José Luis Fillat Comenge; Donald P. Morgan; Molly Mahar; Skander van den Heuvel (Federal Reserve Bank of New York, 2021)
The Main Street Lending Program was created to support credit to small and medium-sized businesses and nonprofit organizations that were harmed by the pandemic, particularly those that were unsupported by other pandemic-response programs. It was the most direct involvement in the business loan market by the Federal Reserve since the 1930s and 1940s. Main Street operated by buying 95 percent participations in standardized loans from lenders (mostly banks) and sharing the credit risk with them. It would end up supporting loans to more than 2,400 borrowers and co-borrowers across the United States, with an average loan size of 9.5 million and total volume of 17.5 billion. This article describes the facility's goals, its design, the challenges and constraints that shaped its reach, and the characteristics of its borrowers and lenders. We conclude with some lessons learned for future policymakers and facility designers.
Keywords: E51; E65; G21; H12; H81; 330; Main Street Lending Program; COVID-19; credit demand; bank loans; bank capital; smallbusinesses; Federal Reserve lending programs